Analysis of iron aluminide coated beams under creep conditions in high-temperature four-point bending tests. (May 2018) - Nordmann, Joachim; Thiem, Philipp; Cinca, Nuria; Naumenko, Konstantin; Krüger, Manja
Recent research is focused on the possibility to coat a metallic alloy with intermetallics or ceramics to improve wear and corrosion resistance, as well as creep behaviour at high temperatures, next to other properties of the alloy. Nowadays, this gains importance due to stricter environment guidelines. Here, we present a model to describe a non-symmetric compound in a high-temperature four-point bending test, performed at400 ° C . The substrate material is an aluminium alloy AlSi10MgT6, and the coating material is the iron aluminide Fe24Al0.6Nb. Up next, a layer-wise theory is introduced to calculate the forces between substrate and coating. Furthermore, required material parameters are identified, and a new procedure to determine Young's modulus of a coating is presented. Finally, simulation results are compared to experimental data, illustrating that the presented model is able to describe the material behaviour accurately.